Reaching Across the DMZ: Identity Uncertainty and Reunification on the Korean Peninsula. Issue 3 (7th April 2015) - Jung, Jiin; Hogg, Michael A.; Choi, Hoon‐Seok
Abstract : Drawing on uncertainty‐identity theory (Hogg, 2012), we explore the effects of uncertainty concerning a specific social identity on group identification and attitudes toward subgroup integration and separation in South Koreans' nested identity context ( N  = 148). All variables were measured. Path analysis revealed, as predicted, that superordinate identity uncertainty weakened superordinate identification and subgroup identity uncertainty weakened subgroup identification. We also found that subgroup identity uncertainty strengthened superordinate identification. This effect was stronger for those who perceived their superordinate group prototype and subgroup prototype to be distinct and nonoverlapping. Furthermore, superordinate identity uncertainty decreased reunification intentions by weakening superordinate identification. Subgroup identity uncertainty increased reunification intentions by strengthening superordinate identification only for those who perceived their superordinate group prototype and subgroup prototype to be distinct and nonoverlapping. Implications for uncertainty identity theory and intergroup relations are discussed.